Identification of a marker indicative of dairy faecal contamination in the environment : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science, Massey University, Palmerston North, New Zealand - Harvey, Stephanie Adele (Massey University, 2001)
Faecal contamination of aqueous environments remains a significant environmental problem. Faecal pollution causes degradation of both chemical and microbial water quality, exposing the public to a variety of pathogenic organisms. Contamination may originate from direct and indirect faecal sources. Direct sources of faecal contamination include piggery and dairy pond effluents, sewage, birds, bathers, or grazing animals with direct access to waterways. Indirect sources may comprise agricultural run-offs, or leaking septic tanks or sewage distribution systems. Discrimination of the origin of faecal contamination would enable monitoring agencies to predict associated disease risks more accurately, as well as implement strategies to mitigate the contaminating source. Escherichia coli, faecal coliforms and enterococci are extensively used as indicators of faecal pollution in water. These organisms are, however, widely distributed in the intestines of warm-blooded animals and hence enumeration does not define faecal origin. It has been suggested that bacterial strains may adapt to their environmental niche and consequently, host association of strains may be apparent. The development of highly discriminatory molecular fingerprinting techniques provides an opportunity to distinguish closely related strains. These techniques may be suitable for locating host associative factors and hence defining the source of faecal contamination. The scope the research described in this thesis was to develop a method capable of discriminating sources of faecal contamination in the environment. Agricultural faecal sources were primarily targeted as they represent a significant source of faecal contamination in New Zealand waterways. Two molecular fingerprinting techniques — Randomly Amplified Polymorphic DNA and Amplified Fragment Length Polymorphism — were investigated for their ability to detect genotypic markers in E. coli. A polymorphic fragment (714 bp) indicative of dairy cattle faecal isolates was identified by AFLP analysis. To facilitate rapid screening of isolates, PCR primers were designed to amplify a segment (462 bp) of the polymorphic fragment. The marker was specific for dairy cattle faecal isolates and was present in approximately half of the strains. Field study results demonstrated that the marker provided a feasible approach for monitoring "special interest" samples such as monitoring significant pollution incidences, supporting prosecution cases or identifying an illusive source of persistent water quality degradation at a particular site. In these instances the diagnostic marker may assist by verifying or eliminating suspected contaminating sources. AFLP analysis was used to locate a marker diagnostic of faecal origin, and indicated that further markers could be identified. Although RAPD-PCR analysis did not locate a diagnostic marker, the technique appeared to corroborate the AFLP results. The inability to obtain a highly specific marker using RAPD analysis may have been a function of the limited primer combinations that were screened. The AFLP technique could be used to construct a library of markers, enabling differentiation of a wide range of contaminating sources.
Keywords: Feces Analysis; Indicators (Biology); Water quality biological assessment; Water quality management